Mechanisation status of oil palm nursery and field cultivation in West Malaysia - Yahya, Azmi; Hassan, Haslina; Adam, Nor Mariah; Pebrian, Darius El; Mat Su, Ahmad Suhaizi (Lembaga Minyak Sawit Malaysia, 2025)
Implementation of mechanisation has been the prime need for the Malaysian palm oil industry in order to reduce its foreign labour dependency. Mechanisation Index (MI) was used in this study to quantify the current mechanisation status in both oil palm seedling production and oil palm field cultivation. It was computed according to the expression of the ratio of machine energy to the total human and machine energy utilised in conducting the involved operations. The obtained average overall MI based on the 10 common clusters of operations in the oil palm FFB production was 0.43. The average overall MI for nursery operation was slightly lower than that of field cultivation operation (i.e., MI values of 0.36 vs. 0.41). The three most critical operations for mechanisation in the oil palm field cultivation operation were the FFB harvesting, which included pruning operation (0.08), rat control operation (0.06) and loose fruit infield collection operation (0.09). The MI values approaching zero reflect the extent of human labour dependency on the method used in the field operations, signifying their seriousness. In general, the obtained MI values provide useful information for developing a workable mechanisation strategy that aligns with the specific circumstances of crop production.